The Efficacy of Pedagogical Modeling in Developing Arabic Speaking Skills (Maharah al-Kalam): A Case Study - K.M.A Ahamed Zubair (Indonesian Journal of Arabic Education and Learning, 2026)
This study investigates the efficacy of pedagogical modeling in developing Arabic speaking skills (maharah al-kalam) within a formal university setting. Conducted as a qualitative case study in the Department of Arabic at The New College, Chennai, data was collected from 30 students and 5 faculty members via interviews, observation, and document analysis. Findings indicate that systematic instructor modeling, embedded within a supportive institutional linguascape (bi'ah lughawiyah), significantly enhances student confidence and communicative fluency. Key strategies include creating Arabic-speaking zones, structured vocabulary immersion, and peer-support mechanisms. Challenges include managing student proficiency diversity and external linguistic interference. The study concludes that consistent pedagogical exemplarity is a critical variable in transforming the classroom into an effective immersive acquisition environment, bridging theory and practice.